PERANCANGAN SISTEM INFORMASI PERPUSTAKAAN DI SEKOLAH TINGGI ILMU KOMPUTER CIPTA KARYA INFORMATIKA - Srisulistiowati, Dwi Budi (Universitas Dirgantara Marsekal Suryadarma, 2015)
STIKOM CKI Library is one of a small library in the environment STIKOM CKI. STIKOM CKI Library is a library that is used to support teaching and learning process conducted by STIKOM CKI. To facilitate and streamline tasks, STIKOM CKI has an Education Information System which can provide various kinds of knowledge that can be used as a basis for broad opening. However, in the passage of this Pendidikan Information system still has many shortcomings. Many process piping from a library that has not been executed. The purpose of this paper is to be able to run and streamline the process of borrowing in a library, among others, book online or ordering online.